Silos to Synergy: Harnessing Integrated Learning for Improved Outcomes - Chandrasekaran, Jeyamala; Pandeeswari, S. Thiruchadai; Pudumalar, S. (Journal of Engineering Education Transformations, 2025)
In recent days, integrated learning emerges as a potent pedagogical approach, intertwining diverse subjects to foster comprehensive education for millennial learners. Its benefits span across enhanced learning outcomes, improved critical thinking, creative problem solving, and engaged learning. The research study aims to create an effective integrated learning experience for the undergraduate students of information technology program. Around 65 students of fifth semester B.Tech IT program and three faculty members have participated in the research study. Project-Based Learning (PBL) has been adapted to creating meaningful cross-curricular experiences. The proposed PBL enables the learners to develop simulations for various cryptographic algorithms which were learnt in the course on Information security. The project also intertwines the concepts covered in other courses like Web Technologies, Software Testing and System Thinking. The PBL has been carefully designed with focus on problem statements, learning goals, project milestones, calendar and rubrics for assessment. Simulations developed by the learners in teams are integrated to create a complete software package which could serve as a virtual lab for cryptography and information security course. The experimental study on integrated learning has resulted in a usable educational software product for teaching cryptographic algorithms. Also, there is a significant enhancement in the attainment of course outcomes and satisfaction index of the learners. The positive outcome in learning achievements and student engagement affirm integrated learning’s value. Various plans to address the implementation challenges in integrated learning are also discussed in the research article. The authors believe that the manuscript will serve as a beginner’s guide to academicians wishing to practice integrated learning in their classrooms.